A new insight into vacancy modulation in lead-doped tungsten oxide nonarchitect for photoelectrochemical water splitting: An experimental and density functional theory approach - Ali, Rana Basit; Lee, Young Jae; Sial, Qadeer Akbar; Duy, Le Thai; Seo, Hyungtak (Journal of Colloid and Interface Science, 2024)
In this study, the impact of lead (Pb) doping on the photoelectrochemical (PEC) water splitting performance of tungsten oxide (WO3) photoanodes was investigated through a combination of experimental and theoretical approaches. Pb-doped WO3 nanostructured thin films were synthesized hydrothermally, and extensive characterizations were conducted to study their morphologies, band edge, optical and photoelectrochemical properties. Pb-doped WO3 exhibited efficient carrier density and charge separations by reducing the charge transfer resistance. The 0.96 at% Pb doping shows a record photocurrent of ∼ 1.49 mAcm−2 and ∼ 3.44 mAcm−2 (with the hole scavenger) at 1.23 V vs. RHE besides yielding a high charge separation and Faradaic efficiencies of ∼ 86 % and > 90 %, respectively. A shift in the Fermi level towards the conduction band was also observed upon the Pb doping. Additionally, density functional theory (DFT) simulations demonstrated the changes in the density of states and bandgap upon Pb doping, exhibiting favorable changes in the surface and bulk properties of WO3.
Keywords: Charge-separation; Density functional theory studies; Density-functional-theory; Experimental approaches; Lead; Pb doping; Performance; Photo-anodes; Photoelectrochemical water splitting; Water splitting; Band structure; DFT studies; Lead; Water splitting; WO3